Untapped Potential of Citizen Science in Mexican Small-Scale Fisheries - Fulton, Stuart; López-Sagástegui, Catalina; Weaver, Amy Hudson; Fitzmaurice-Cahluni, Fernanda; Galindo, Carlos; Fernández-Rivera Melo, Francisco; Yee, Silvia; Ojeda-Villegas, María Belén; Fuentes, David Antonio; Torres-Bahena, Elizabeth (Frontiers in Marine Science, 2019)
Citizen science is a rapidly growing field with well-designed and run citizen science projects providing substantial benefits for conservation and management. Marine citizen science presents a unique set of challenges and lags behind terrestrial citizen science, but also provides significant opportunities to work in data-poor fisheries. This paper analyses case studies of citizen science projects developed in collaboration with small-scale fishing communities in Mexico´s Pacific Ocean, Gulf of California and Caribbean Sea. The design and performance of these projects were evaluated against the previously published Ten Principles of Citizen Science, and Scientific Stages of Inquiry. Our results suggest that fisheries monitoring, submarine monitoring of no take zones, oceanographic monitoring, and the use of species identification apps by fishers meet the requirements of the published guidelines and are effective tools for involving the small-scale fishing community in science. Translating effective citizen science projects in to effective fishery management however is still at an early stage. Whilst citizen science data have been used locally by communities to adapt fishing practices, calculate recommendations for total allowable catches, establish and evaluate no take zones and detect range extensions of species affected by climate change, challenges remain regarding how to garner official recognition for the data, incorporate these growing sources of data into national policy, and use the data for adaptive management regimes at the national level.